Synthesis and antiviral properties derivatives of 1-(para-tolyl)-4-aryl-5,6,7,8-tetrahydro-2,2a,8a-triazacyclopenta[cd]azulene-3-carbothioic acid arylamides - S. A. Demchenko; Yu. A. Fedchenkova; А. М. Іvаsеnко; V.V. Sukhoveev; A. M. Demchenko (The State Expert Center of the Ministry of Health of Ukraine, 2019)
Nowadays, H1N1 - strain of so called «swine» or «mexican» subspecie A virus, which is still not studied, and which spreads through aerosol and contact is known to many world countries. Significant number of lethal cases during influenza pandemic season in Ukraine was observed. It should be noted, that patients went to the hospitals in very severe cases, which is why registered daily lethality is in 31,6% of cases. Everything listed above had made it necessary to conduct preventive measures on global and national levels. One of such measures is creation of new direct action medicinal agents. The goal of this work was the synthesis of compounds with potential antiviral properties in variety of 5,6,7,8-tetrahydro-2,2a,8a-triazacyclopenta[cd]azulen-3-carbotionic acid derivatives. We have chosen derivatives of 5,6,7,8-tetrahydro-2,2a,8a-triazacyclopenta[cd]azulen-3-carbotionic acid (6 a-e and 7 a-h), which were synthesized by boiling of 1-(para-tolyl)-4-aryl-5,6,7,8-tetrahydro-2,2a,4a-triazacyclopenta[cd]azulenes (5a or 5b) with corresponding arylisothiocyanates in dry benzene. Antiviral activity of phenylamid 1-(para-tolyl)-4-phenyl-5,6,7,8-tetrahydro-2,2a,8a-triazacyclopenta[cd]azulen-3-carbotionic acid against Flu A H1N1 California/07/2009 was researched in Southern Research Institute - SRI, Birmingham, Alabama). Variety of new derivatives of 5,6,7,8-tetrahydro-2,2a,8a-triazacyclopenta[cd]azulen-3-carbotionic acid. Composition and structure of all synthesized compounds are proven by data of element analysis and 1Н NMR spectroscopy. In conducted researches of antiviral activity of phenylamide 1-(para-tolyl)-4-phenyl-5,6,7,8-tetrahydro-2,2a,8a-triazacyclopenta[cd]azulen-3-carbotionic acid against Flu A H1N1 California/07/2009, it was found out, that synthesized compound shows pronounced antiviral activity, compared to reference medicinal agents Ribavirin and Amizon. Therefore, conducted researches confirm perspective of development of a new domestic medicinal agent with antiviral activity, based on derivatives of 5,6,7,8,-tetrahydro-2,2a,8a-triazacyclopenta[cd]azulen-3-carbotionic acid.